Factors Influencing Profitability of Commercial Banks in Tanzania: A Case Study of CRDB Bank Plc - Jilenga, Moga Tano; Luanda, Patrick (The Economics and Finance Letters, 2021)
This study examines factors influencing profitability of commercial banks in Tanzania. This study uses the CRDB Bank Plc. as a case study to investigate the bank specific factors and macroeconomic factors on bank profitability. The study uses correlational research design to examine the bank-specific factors and macroeconomic factors on profitability. Time series data for the period spanning from 2008 to 2019 were used. The results indicate that bank-specific factors such as bank deposit, non-performing loans and bank expense are statistically significant on bank profitability. On the other hand, macroeconomic factors were found to be insignificant on bank profitability. The implication for this study is that commercial banks policies should be geared towards bank-specific factors in enhancing profitability rather than concentrating on macroeconomic factors which does contribute to bank’s profitability. The bank deposits mobilized should be used effectively in realizing profitability. In addition, bank expenses should be cost effective in order to enhance bank profitability.